Transboundary aquifer mapping and management in Africa: a harmonised approach - (:unkn) unknown (My University, 2013)
Recent attention to transboundary aquifers (TBAs) in Africa reflects the growing importance of these resources for development in the continent. However, relatively little research on these aquifers and their best management strategies has been published. This report recapitulates progress on mapping and management frameworks for TBAs in Africa. The world map on transboundary aquifers presented at the 6th World Water Forum in 2012 identified 71 TBA systems in Africa. This report presents an updated African TBA map including 80 shared aquifers and aquifer systems superimposed on 63 international river basins. Furthermore, it proposes a new nomenclature for the mapping based on three sub-regions, reflecting the leading regional development communities. The map shows that TBAs represent approximately 42 % of the continental area and 30 % of the population. Finally, a brief review of current international law, specific bi- or multilateral treaties, and TBA management practice in Africa reveals little documented international conflicts over TBAs. The existing or upcoming international river and lake basin organisations offer a harmonised institutional base for TBA management while alternative or supportive models involving the regional development communities are also required. The proposed map and geographical classification scheme for TBAs facilitates identification of options for joint institutional setups.
Keywords: African Research